Evaluation of Free - Payment School Implementation at Senior High School / Islamic Senior High School and Vocational School in the Regency of Ogan Komering Ilir - ., Taslim; Sujanto, Bedjo; ., Hamidah (International Journal of Scientific Research and Management (IJSRM), 2018)
This research is concerned on the evaluation of how the policy of free payment school at senior high school / islamic senior school and vocational school in the regency of  ogan komering ilir are implemented through CIPP model which was develop by Stufflebeam’s.  The aim of the research is to dig comprehensively the implementation of the above policy.The findings of the evaluation obtained: (1) context, program is covering all the main needs, regulations, goals, are fulfill so that the program possibly to be implemented, (2) the input, human resources, budget, strategy, the structure of the organization, infrastructures, and procedure are available, (3) the process, communication, attitude of the program implementers, and bureaucracy are well built, (4) the product of the program are helping to ease the parent’s from the school cost and to improve the quality, welfare, and the school performance.